Lisina para tilápia do Nilo: efeito de duas estratégias de formulação e respostas de duas gerações de um programa de melhoramento genético - Gabriel Francisco de Oliveira Alves (2020)
The objective was to evaluate the effect of two formulation strategies in studies to determine lysine requirements and also the responses of fish with different growth potential in relation to increasing levels of lysine. In Experiment I, the response of Nile tilapia juveniles from 20.0 to 160.0 g was evaluated on diets with increasing levels of lysine (1.50; 1.74; 1.98; 2.22; 2.46 and 2.70%) and formulated using the amino acid supplementation technique (SUP) and amino acid supplementation technique using the ideal protein concept (SPI). In Experiment II, the growth and survival responses of Nile tilapia post-larvae from two generations of a breeding program were evaluated, one of which was fast-growing (G5) and the other of slow-growing (G0), receiving diets with different levels of lysine (1.43; 1.80; 2.02; 2.42 and 2.68%). The diets were provided five and nine times a day, in experiments I and II, respectively. Both works were carried out in a water recirculation system. In Experiment I, no differences were observed for the final average weight, daily weight gain, feed conversion and protein retention efficiency as a function of lysine levels or formulation strategies (P > 0.05). Feed intake (CR) was affected by lysine levels, according to the Kruskal-Wallis test (P < 0.05). However, the CR did not show a clear trend in relation to lysine levels in the diet. The consumption of lysine per kilogram of metabolic weight gain (CLM) differed in terms of lysine levels and formulation technique, with less CLM for fish that received diets formulated using SPI. Body composition, on the other hand, showed no changes (P > 0.05). In Experiment II, survival did not differ between G0 and G5 (P > 0.05). In general, G5 fish showed better growth responses in relation to G0 and the interaction Lysine X Generation was identified only for feed consumption, with linear behavior for G0 and quadratic for G5. Based on the average weight at 28 and 56 days of age, the quadratic regression models indicated 2.4374 and 2.6773% of lysine in the diet, respectively, for the post-larvae of both generations.